COVID-19–Associated Bone Marrow Necrosis—A Case Report - Ghosh, Soumyadeep; Gupta, Santosh S.; Mehta, Nirad; Khodaiji, Shanaz (Indian Journal of Radiology and Imaging, 2021)
We report, herein, a rare case of vertebral bone marrow necrosis in a patient at 1-month post–novel coronavirus disease 2019 (COVID-19) pneumonia complicated with disseminated intravascular coagulation (DIC). The commonly observed radiological features on the imaging modalities like computed tomography (CT), magnetic resonance imaging (MRI), and 18-F fluorodeoxyglucose positron emission tomography (FDG PET) have been discussed here followed by a brief discussion on the role of in-phase and opposed-phase imaging in differentiating the disease from malignant infiltrative pathologies. Histopathological findings on bone marrow smear that confirm the diagnosis have also been illustrated.
Keywords: avascular necrosis; bone marrow necrosis; chemical shift imaging; computed tomography; COVID-19; disseminated intravascular coagulation; opposed phase; magnetic resonance imaging; opposed phase; positron emission tomography; signal intensity index